Science And Its Role In Changes In Islamic Legal Thought (An Analysis Of Changes In The Fatwa Of The Indonesian Ulema Council Due To Recent Scientific Findings) - Rasyid, Muhammad; Muhsin Aseri; Sukarni; Akh. Fauzi Aseri; Muhammad Syazwan Faid (Syariah: Jurnal Hukum dan Pemikiran, 2023)
Abstract: This study argues that scientific findings play a role in encouraging changes in the fatwas of the Indonesian Ulema Council (MUI). This research is library research that takes the fatwas of the Indonesian Ulema Council (MUI) as its primary source. Those fatwas are Fatwa on Vasectomy/Tubectomy, Fatwa on Meningitis Vaccine for Hajj and Umrah Jama'ah, Fatwa on Determination of the Beginning of Ramadan, Shawwal and Dhulhijjah, and Fatwa on Qibla Direction. Data collection was conducted using document study techniques. The data analysis is done with the content analysis method. The results of this study show that scientific findings play an important role in encouraging changes in MUI fatwas into three patterns of change, namely: First, rukhsah, which is the change of fatwa in the form of giving leeway to the legal provisions of the previous fatwa, as the change of MUI fatwa on vasectomy/tubectomy. Second, nasakh is the change of fatwa in the form of eliminating/canceling the legal provisions in the previous fatwa, such as the change of MUI fatwa on Meningitis Vaccine for Hajj and Umrah Jama'ah. Third, takmîl is the change of fatwa in the form of perfecting/completing the legal provisions in the previous fatwa, as the change of MUI fatwa on the determination of the beginning of Ramadan, Shawwal and Dhulhijjah, and fatwa on Qibla direction. Methodologically, in addition to considering the latest scientific studies, MUI fatwas are also equipped with shara' arguments including adequate verses of the Qur'an, Hadith, scholarly opinions, and ushul fiqh studies. Keyword: Science, Change, Fatwa, MUI